The influence of attitude, perceived behaviour control, subjective norms and self-identity towards zero waste behaviour of consumers in the Klang Valley - Mustafa, Fazlina Akmal; Muhammad Arif, Afida Mastura; Abu Bakar, Elistina (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2023)
Managing solid waste is essential to safeguard the environment to ensure its sustainability and consumer quality of life. Consumers can achieve a systematic waste management plan through a strategic zero waste framework. This far-sighted concept is based on the hierarchy of waste management that advocates avoiding excessive consumption, minimizing waste, maximizing recycling and practicing composting so that landfill disposal will be the last option. This study aims to determine the attitude, perceived behaviour control, subjective norms and self-identity as the predictors of zero waste behaviour of consumers. A total of 400 respondents in the Klang Valley area were chosen through stratified random sampling. A self-administered questionnaire was used in collecting the data. The Pearson correlation analysis found that attitude, perceived behaviour control, subjective norm and self-identity had significant relationships with zero waste behaviour. The multiple regression analysis showed that selfidentity is the strongest predictive factor in consumer zero waste behaviour. The findings are beneficial, especially to the relevant agencies that manage solid waste to improve relevant policies and programs. The programs should strengthen consumer self-identity while enhancing their responsibility and commitment to behaviour towards zero waste.